(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Extreme poverty has become the leading cause of chronic and persistent hunger in developing nations. Undernourishment, especially among children and women, is a persistent issue in low-income areas. When people do not get enough of one or more vital nutrients, their physical and mental development and health suffer. Unhealthy eating habits are linked to deficiencies in socially significant nutrients such as those needed for normal growth, development, and freedom of choice in physical exercise and employment